Analysis of Surface Waves Modes in Planar Connected Arrays for Radio Astronomy - Baelemans, R.; Sutinjo, Adrian; Smolders, B.; Davidson, David; Johannsen, U.; Wayth, Randall (2018)
© 2018 IEEE. A planar array of closely spaced capacitively coupled antennas over a ground plane can be designed to have a broadband and smooth response, making it an interesting candidate for a low-frequency radio-astronomy instrument. However, surface wave modes propagating over the array plane can seriously degrade the response. We will show the derivation of a necessary condition for which surface wave modes will propagate along a planar array of closely spaced capacitively connected antennas. The derivation will be based upon the transverse resonance method [2] applied to the equivalent circuit of a unit cell of an infinite capacitively connected array. From the necessary condition a simple design consideration can be derived which would prevent the excitation of unwanted surface waves on the structure. Finally, we will show how adding resistive loading in the form of the low-noise amplifiers can dampen the unwanted surface wave effects.